Gazeta Podlaska . informator NSZZ "Solidarność" Region Mazowsze Oddziały w Siedlcach i Białej Podlaskiej, no. 17, 1988 - Boni, Michał; Anusz, B.; Lewczuk, J. ([s.n.], 1988)
Print run: 1200-4000 copies